Magnesium Isoglycyrrhizinate Alleviates Arsenic Trioxide-Induced Cardiotoxicity: Contribution of Nrf2 and TLR4/NF-κB Signaling Pathway - Zheng B; Yang Y; Li J; Li J; Zuo S; Chu X; Xu S; Ma D; Chu L (Dove Medical Press, 2021)
Bin Zheng,1,* Yakun Yang,1,* Jinghan Li,1 Jing Li,1 Saijie Zuo,1 Xi Chu,2 Shan Xu,3 Donglai Ma,1 Li Chu1,4 1School of Pharmacy, Hebei University of Chinese Medicine, Shijiazhuang, Hebei, 050200, People’s Republic of China; 2Department of Pharmacy, The Fourth Hospital of Hebei Medical University, Shijiazhuang, Hebei, 050011, People’s Republic of China; 3Hebei Province Hospital of Chinese Medicine, Affiliated Hospital of Hebei University of Chinese Medicine, Shijiazhuang, Hebei, 050200, People’s Republic of China; 4Hebei Key Laboratory of Integrative Medicine on Liver-Kidney Patterns, Hebei University of Chinese Medicine, Shijiazhuang, Hebei, 050200, People’s Republic of China*These authors contributed equally to this workCorrespondence: Donglai Ma; Li ChuSchool of Pharmacy, Hebei University of Chinese Medicine, Shijiazhuang, Hebei, 050200, People’s Republic of ChinaTel/Fax +86 311 89926719Email mdl_hebei@aliyun.com; chuli0614@126.comPurpose: Magnesium isoglycyrrhizinate (MgIG), a single stereoisomer magnesium salt of glycyrrhizic acid, has beneficial effects on the cardiovascular system through anti-inflammatory, anti-oxidation, and anti-apoptotic actions. However, MgIG has not been shown to provide protection against cardiotoxicity induced by arsenic trioxide (ATO). This study aims to demonstrate the protection of MgIG against ATO-induced cardiac toxicity in mice and to investigate the underlying mechanism.Methods: A mouse cardiotoxicity model was established by administering 5 mg/kg ATO for 7 days. MgIG used in conjunction with the ATO to assess its cardioprotection.Results: MgIG administration could significantly reduce reactive oxygen species generation and the changes in tissue morphology. Also, MgIG administration increased the activity of antioxidase, such as superoxide dismutase, catalase, and glutathione peroxidase, and reduced malondialdehyde content and pro-inflammatory cytokine levels. Western blotting showed decreased expression of Bcl-2 associated X protein and Caspase-3, with increased expression of B-cell lymphoma 2. Importantly, MgIG administration increased nuclear factor-erythroid-2-related factor 2 (Nrf2) expression, while the expressions of nuclear factor kappa-B (NF-κB) and toll-like receptor-4 (TLR4) were significantly decreased.Conclusion: Our data showed that MgIG alleviates ATO-induced cardiotoxicity, which is associated to the anti-inflammation, anti-oxidation, and anti-apoptosis action, potentially through activation of the Nrf2 pathway and suppression of the TLR4/NF-κB pathway.Keywords: magnesium isoglycyrrhizinate, arsenic trioxide, cardiotoxicity, Nrf2, TLR4/NF-κB